Optimization in the Energy Industry - Kallrath, Josef; Pardalos, Panos M.; Rebennack, Steffen; Scheidt, Max.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2009)
Today, the optimization of production planning processes using IT and quantitative methods is a de-facto standard in the energy industry. The energy problem is challenging and one of the most important political and economical issues in the world. Governments face the problem how to adopt the system of `Cap and Trade.' Especially, energy consuming industries, like steel, power, oil and chemical, are seriously confronted with this problem. The book offers a broad in-depth overview reflecting the requirements, possibilities and limits of mathematical optimization and, especially, stochastic optimization in the energy industry. 22 chapters with world-wide origins illuminate the mathematical requirements based on practical experiences and provide an ideal insight into the energy world -- from integration of wind energy, chain of errors in nuclear power plants and scheduling of hydroelectric power stations, over risk assessment in trading activities to various mathematical approaches.
Challenges and Perspectives of Optimization in the Energy Industry -- Current and Future Challenges for Production Planning Systems -- The Earth Warming Problem: Practical Modeling in Industrial Enterprises -- Deterministic Methods -- Trading Hubs Construction for Electricity Markets -- A Decision Support System to Analyze the Influence of Distributed Generation in Energy Distribution Networks -- New Effective Methods of Mathematical Programming and Their Applications to Energy Problems -- Improving Combustion Performance by Online Learning -- Critical States of Nuclear Power Plant Reactors and Bilinear Modeling -- Mixed-Integer Optimization for Polygeneration Energy Systems Design -- Optimization of the Design and Partial-Load Operation of Power Plants Using Mixed-Integer Nonlinear Programming -- Optimally Running a Biomass-Based Energy Production Process -- Mathematical Modeling of Batch, Single Stage, Leach Bed Anaerobic Digestion of Organic Fraction of Municipal Solid Waste -- Spatially Differentiated Trade of Permits for Multipollutant Electric Power Supply Chains -- Applications of TRUST-TECH Methodology in Optimal Power Flow of Power Systems -- Stochastic Programming: Methods and Applications -- Scenario Tree Approximation and Risk Aversion Strategies for Stochastic Optimization of Electricity Production and Trading -- Optimization of Dispersed Energy Supply $1 (BStochastic Programming with Recombining Scenario Trees -- Stochastic Model of the German Electricity System -- Optimization of Risk Management Problems in Generation and Trading Planning -- Optimization Methods Application to Optimal Power Flow in Electric Power Systems -- WILMAR: A Stochastic Programming Tool to Analyze the Large-Scale Integration of Wind Energy -- Stochastic Programming in Pricing -- Clean Valuation with Regard to EU Emission Trading -- Efficient Stochastic Programming Techniques for Electricity Swing Options -- Delta-Hedging a Hydropower Plant Using Stochastic Programming.s
Keywords: Mathematics; Energy systems; Operations research; Decision making; Calculus of variations; Electric power production; Mathematics; Calculus of Variations and Optimal Control; Optimization; Energy Systems; Operation Research/Decision Theory; Energy Technology; Electronic books